Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar IPA Kelas V - Roy Martian Ratu (Universitas Negeri Makassar, 2024)
This research motivated by the science learning results of class V UPT SDN 6 North Makale students. One solution to overcome problem use the Problem Based Learning model. The aim research is to improve students science learning outcome at UPT SDN 6 North Makale using Problem Based Learning model. This research method Classroom Action Research which carried in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection, and research time carried in May 2023. Research subjects were 24 fifth grade students, 12 male students, and 12 female students. Data collection techniques include documentation, observation and learning outcomes tests. The results research show that science learning outcomes in class V UPT SDN 6 North Makale in cycle I are classified as good with an average of 70.27. Furthermore, 24 students, only 15 students finished with classical completeness 62.5%. In cycle II classified as good with an average of 80.68 out of 24 students, there were 20 students who finished with classical completeness of 83.3%. This can be concluded that using the Problem Based Learning learning model can improve the learning outcomes of class V UPT SDN 6 North Makale students.